Psychological Perspectives on Religious Education: An Individual Differences Approach - Francis, Leslie J. (Brill research perspectives in religion and education, 2020)
In this publication the contributions made by the individual differences tradition of psychology over the past 50 years to research in religious education are reviewed and assessed. In this context religious education is conceived broadly to embrace what takes place in schools, within religious communities, and within households across the age span. The opening section roots the analysis within the tradition of developmental psychology and the research that flourished in the area of religious development during the 1960s. It is from these foundations that current interest in the individual differences approach emerges. Subsequent sections examine the centrality of the attitudinal dimension of religion, discuss the place of personality in the individual differences tradition, explore sex as a core individual difference in religion, map the correlates, antecedents and consequences of individual differences in religious affect or attitudes, review research into the distinctiveness and effectiveness of church schools and the family in religious nurture, identify the factors that account for individual differences in attitude toward religious diversity, explore the relevance of the individual differences tradition for adult religious education, and explore the implications of the individual differences tradition for biblical hermeneutics and discipleship learning.